Decoherent Excitation of Transverse Free Currents in Dielectric Liquids via Inter-Molecular Interactions - DiLoreto, C. S.; Rangan, C. (Frontiers in Physics, 2021)
We present a theoretical model for a class of optical scattering experiments in which short-duration, linearly-polarized electromagnetic pulses scatter off dielectric liquids. The pattern of scattering, particularly in the transverse direction, indicates that significant free currents are generated in the direction orthogonal to the polarization of the incident light. Modelling the target as a dense cluster of two-level systems, we show that transverse free currents are produced by short duration, electric-dipole interactions between proximate molecules, and result in scattering patterns similar to those observed in the experiments. Calculations provide a rationale for why these scattering patterns are not observed in the same molecules at lower densities or with lower field intensities. These features make this model a relevant alternative to proposed transverse optical magnetism theories.